The Effects of Different Challenge-Level Balance Tasks on Stroke Cortical Responses and Balance Assessment Using EEG - Rui Xu; Yu Bai; Jun Liang; Ningning Wang; Yongzheng He; Lin Meng; Dong Ming (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Previous studies have validated that different balance tasks induce different cortical responses, which are key indexes of balance assessment. Assessing balance is crucial for stroke survivors to prevent falls and improve rehabilitation outcomes. However, it was unclear whether these tasks may affect the balance assessment, particularly regarding the relationship between task difficulty and the corresponding cortical responses involved in balance control. Therefore, we sought to explore the effects of different challenge-level balance tasks on balance assessment. Eighteen participants with stroke and thirteen healthy individuals were recruited in this study. The EEG was collected during sitting, standing and perturbation tasks. The pairwise-derived Brain Symmetry Index (pdBSI), and Granger Causality (GC) were analyzed with a two-way (task $× $ group) RMANOVA. Finally, a multiple linear regression analysis was applied to predict the BBS score with the above parameters. We found a significant interaction effect on pdBSI and GC. In the frontal lobe, participants with stroke exhibited significantly higher pdBSI (standing: p =0.042, perturbation: p =0.013) and lower GC (standing: p <0.001, perturbation: p =0.028) compared to healthy controls. Similarly, in the parietal lobe, stroke survivors showed markedly higher pdBSI (standing: p =0.006, perturbation: p=0.012) and lower GC (standing: p=0.030, perturbation: p=0.011). Finally, The Berg Balance Scale (BBS) scores could be reliably predicted using parietal BSI and frontal GC metrics recorded during standing (p <0.001, adjusted R $^{{2}}=0.938$ ) and perturbation tasks (p =0.001, adjusted R $^{{2}}=0.644$ ). It was discovered that the more challenging balance tasks better revealed the difference in the power distribution and the directional functional connection between groups. The pdBSI and GC during standing and perturbation tasks, could be used as biomarkers for stroke balance assessment.